2014
DOI: 10.26456/mmg/2014-211
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of 6ΛHe hypernucleus within configuration space Faddeev approach

Abstract: The cluster 4 He + Λ + n model is applied to describe the 6 Λ He hypernucleus. The consideration is based on the configuration space Faddeev equations for a system of non-identical particles. A set of the pair potentials includes the OBE simulating (NSC97f) model for the Λn interaction and the phenomenological potentials for the αΛ and αn interactions. We calculated energies of spin (1 − ,2 − ) doublet. For the 2 − excitation energy, the obtained value is 0.18 MeV. The hyperon binding energy of the bound 1 − s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…It is thus interesting to see if the existence of a resonance just below or above the threshold, as it has been found by the HAL QCD Collaboration [9] and low-energy effective field theory studies [10], may affect the position of the three-body S wave resonance found in Ref. [20]. For this purpose, we have now constructed separable potential models of the , , and amplitudes reproducing the behavior of the HAL QCD collaboration results [9].…”
Section: (A) Of Ref [19]mentioning
confidence: 85%
See 4 more Smart Citations
“…It is thus interesting to see if the existence of a resonance just below or above the threshold, as it has been found by the HAL QCD Collaboration [9] and low-energy effective field theory studies [10], may affect the position of the three-body S wave resonance found in Ref. [20]. For this purpose, we have now constructed separable potential models of the , , and amplitudes reproducing the behavior of the HAL QCD collaboration results [9].…”
Section: (A) Of Ref [19]mentioning
confidence: 85%
“…[12], we developed a model in Ref. [20] of the three-body system, which allowed us to look for possible three-body resonances. Using separable two-body interactions fitted to the low-energy data of the Nijmegen S wave baryon-baryon Ξd ΞNN NN amplitudes [16][17][18], we found a resonance just below the threshold with a very small width of only 0.09 MeV.…”
Section: (A) Of Ref [19]mentioning
confidence: 99%
See 3 more Smart Citations